PENGARUH KUALITAS PELAYANAN DAN PENGETAHUAN PERPAJAKAN PADA PERILAKU KEPATUHAN WAJIB PAJAK DENGAN NIAT SEBAGAI PEMODERASI - Dicriyani, Ni Luh Gede Mahayu; Budiartha, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
ABSTRACT The purpose of this research at sector wholesale and retail; repair of car and motorcycles is to find and get empirical evidence influence the quality of tax and taxpayers behavior on conduct compliance taxpayers, intention taxpayers moderating influence the quality of tax on conduct compliance taxpayers and intention taxpayers moderating influence knowledge set in compliance taxpayers behavior.The data used was primary data gathered to technique survey with the questionnaire. Analysis techniques the data used was moderation regression (MRA) analysis. The determination of sample done with the probability to technique purposive sampling. The total sample used as many as 83 taxpayers body enrolled in the tax office Madya Denpasar. The results showed that the quality of the tax service has not been affecting the behavior compliance taxpayers, knowledge taxation impact on behavior compliance taxpayers, intention taxpayers strengthen the influence of the quality of tax service on conduct compliance taxpayers and intention taxpayers weakened the influence of knowledge tax on conduct compliance taxpayers.
Keywords: intention, behavior compliance taxpayers